The Effect of Good Corporate Governance and Corporate Social Responsibility on Tax Avoidance - Grace Tamara Pretty Putri Fajar; Rustam, Akie Rusaktiva (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2024)
The research was conducted to find out whether Good Corporate Governance (GCG) as proxied by the board of directors, independent commissioners and audit committees and Corporate Social Responsibility (CSR) as measured using CSRDI affect tax evasion as measured using the GAAP ETR. This research method is quantitative and supported by multiple regression analysis using SPSS 24 software. The samples used were 121 companies engaged in the FMCG sector which were listed on the IDX during the 2020-2022 range. The sample selection used purposive sampling method. The data that researchers use is secondary data obtained through the official IDX website. This study found that if the proportions of the board of directors, independent commissioners, audit committee, and the value of CSRDI simultaneously have a significant effect on tax avoidance partially, the board of directors does not have a significant effect on tax avoidance. Meanwhile, the proportion of independent commissioners and the CSRDI value has a significant negative effect on tax avoidance. Meanwhile, the audit committee has a significant and positive impact on tax avoidance in FMCG companies listed on the IDX for the 2020-2022 period.   Abstrak Penelitian dilakukan guna mengetahui apakah Good Corporate Governance (GCG) yang diproksikan oleh dewan direksi, komisaris independen serta komite audit dan Corporate Social Responsibility (CSR) yang diukur mempergunakan CSRDI memengaruhi penghindaran pajak yang diukur menggunakan GAAP ETR. Metode penelitian ini adalah kuantitatif dan didukung oleh analisis regresi berganda menggunakan software SPSS 24. Sampel yang dipergunakan sejumlah 121 perusahaan yang berkecimpung di sektor FMCG yang tercatat di BEI selama rentang 2020-2022. Pemilihan sampel mempergunakan metode purposive sampling. Data yang peneliti gunakan, yaitu data sekunder yang didapat melalui situs resmi BEI. Penelitian ini menemukan bila proporsi dewan direksi, komisaris independen, komite audit, serta nilai dari CSRDI secara simultan memiliki pengaruh signifikan bagi tax avoidance secara parsial, dewan direksi tidak memengaruhi signifikan bagi tax avoidance. Sementara proporsi komisaris independen dan nilai CSRDI memengaruhi secara signifikan negatif bagi tax avoidance. Sementara komite audit memengaruhi signifikan dan positif bagi tax avoidance pada perusahaan FMCG yang tercatat di BEI periode 2020-2022.